Perception of Consumer Purchasing Decisions based on Brand Image and Location (Case study at a fashion store in Bandung City) - Vini Sapitri Pebriani; Irena Larashati (Kontigensi : Jurnal Ilmiah Manajemen, 2020)
The rapid development of Muslim fashion in Indonesia, making Indonesia a leading Muslim fashion trend. With so many young Indonesian designers introducing Muslim fashion throughout the world and succeeding in kicking off fashion, able to make homeland mode the world's spotlight. The method used in this research is descriptive and verification methods. The samples taken in this study were respondents who were consumers of Mezora Buah Batu Bandung with 96 respondents with accidental sampling technique. The results showed the direct effect of brand image by 5.5%, while the indirect impact was 8.1%, so that the total effect of brand image on purchasing decisions was 13.6%. For the location effect directly 42.5%, while the indirect effect is 8.1%. So the total influence of Location on purchasing decisions is 50.6%. The results showed that the variable Brand image (X1) and Location (X2) simultaneously influence the purchase decision with a total influence of 64.2%. In comparison, the remaining 35.8% influenced by other variables outside this study.